2011
DOI: 10.1002/pola.25066
|View full text |Cite
|
Sign up to set email alerts
|

R‐RAFT approach for the polymerization of N‐isopropylacrylamide with a star poly(ε‐caprolactone) core

Abstract: Reversible addition-fragmentation chain transfer (RAFT) polymerization is a more robust and versatile approach than other living free radical polymerization methods, providing a reactive thiocarbonylthio end group. A series of well-defined star diblock [poly(e-caprolactone)-b-poly(N-isopropylacrylamide)] 4 (SPCLNIP) copolymers were synthesized by R-RAFT polymerization of N-isopropylacrylamide (NIPAAm) using [PCL-DDAT] 4 (SPCL-DDAT) as a star macro-RAFT agent (DDAT: S-1-dodecyl-S 0 -(a, a 0 -dimethyl-a 00 -acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 68 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…[8][9][10][11] The core-first strategy enables two distinct synthetic routes: the Z-group approach in which thiocarbonylthio groups are linked to the core via the "stabilizing" Z-group of the chain transfer agent (CTA), [8][9][10][11][12][13][14][15][16][17][18] and the R-group approach, in which the thio entity is attached to the core via the "leaving" R-group of the CTA. [19][20][21] On the other hand, over the last decade, particular attention has been given to temperature-sensitive polymers because of their potential applications. Two of the most studied thermosensitive polymers are poly(N-isopropylacrylamide) (PNIPAM) 22 and poly(N-vinylcaprolactam) (PNVCL) 23,24 ; both polymers are water-soluble below their LCST, are nonionic, and exhibit a LCST around the physiological range (Fig.…”
mentioning
confidence: 99%
“…[8][9][10][11] The core-first strategy enables two distinct synthetic routes: the Z-group approach in which thiocarbonylthio groups are linked to the core via the "stabilizing" Z-group of the chain transfer agent (CTA), [8][9][10][11][12][13][14][15][16][17][18] and the R-group approach, in which the thio entity is attached to the core via the "leaving" R-group of the CTA. [19][20][21] On the other hand, over the last decade, particular attention has been given to temperature-sensitive polymers because of their potential applications. Two of the most studied thermosensitive polymers are poly(N-isopropylacrylamide) (PNIPAM) 22 and poly(N-vinylcaprolactam) (PNVCL) 23,24 ; both polymers are water-soluble below their LCST, are nonionic, and exhibit a LCST around the physiological range (Fig.…”
mentioning
confidence: 99%
“…In contrast, RDRP techniques are relatively robust and therefore allow for a convenient fabrication of amphiphilic star polymers. 19,21,[33][34][35][36][37][38][39] Radical addition fragmentation chain transfer (RAFT) polymerisation in particular tolerates a large variety of functional monomers and is relatively undemanding in terms of experimental setup, as only a chain transfer agent (CTA) is added to a classical FRP mixture.…”
Section: -24mentioning
confidence: 99%
“…On the other hand, a significant shortening of the induction period and an increase in the apparent propagation rate in the RAFT polymerization of MMA were observed, resulting in higher mole fractions of the PMMA block than those of the PLA block. Bian et al 21 reported a similar phenomenon from the RAFT polymerization of NIPAM at 100 C using star-shaped PCL macro-RAFT agents (SPCL-RAFTs). The RAFT polymerization rate of NIPAM using SPCL 25 -RAFT was higher than that using SPCL 10 -RAFT.…”
Section: Figurementioning
confidence: 78%